Risk factors for post‐transplant lymphoproliferative disorder after Thymoglobulin‐conditioned hematopoietic cell transplantation. Issue 1 (1st December 2017) - Kalra, Amit; Roessner, Cameron; Jupp, Jennifer; Williamson, Tyler; Tellier, Raymond; Chaudhry, Ahsan; Khan, Faisal; Taparia, Minakshi; Jimenez‐Zepeda, Victor H.; Stewart, Douglas A.; Daly, Andrew; Storek, Jan
Abstract: Epstein‐Barr virus (EBV)‐induced post‐transplant lymphoproliferative disorder (PTLD) occurs frequently when rabbit antithymocyte globulin (ATG) is used in hematopoietic cell transplant (HCT) conditioning. We retrospectively studied 554 patients undergoing ATG‐conditioned myeloablative HCT. Strategies used to minimize mortality due to PTLD were either therapy of biopsy‐diagnosed PTLD in the absence of EBV DNAemia monitoring (n = 266) or prompt therapy of presumed PTLD (based on clinical/radiologic signs and high EBV DNAemia, in the setting of weekly EBV DNAemia monitoring) (n = 199). Both strategies resulted in similar mortality due to PTLD (0.7% vs 1% at 2 years, P = .43) and similar overall survival (63% vs 67% at 2 years, P = .23) even though there was a trend toward higher PTLD incidence with the prompt therapy. Donor positive with recipient negative EBV (D+R−) serostatus was a risk factor for developing PTLD. Older patient age, HLA‐mismatched donor, and graft‐versus‐host disease were not associated with increased risk of PTLD. In summary, in ATG‐conditioned HCT, D+R− serostatus, but not older age, mismatched donor or GVHD is a risk factor for developing PTLD. EBV DNAemia monitoring may be a weak risk factor for developing/diagnosing PTLD; the monitoring coupled with prompt therapy does not improve survival.